ANALISIS KOMPETENSI ABAD-21 DALAM BIDANG KOMUNIKASI PENDIDIKAN - Nurjanah, Siti Ahadiah (Gunahumas, 2019)
ABSTRAKAbad 21 ditandai dengan berkembangnya informasi, komputasi, otomasi, dan komunikasi yang merambah dalam segala aspek kehidupan manusia di semua belahan dunia. Hal ini tentunya berdampak pada pendidikan yang diterapkan termasuk di dalamnya bagaimana model pembelajarannya sehingga dapat mengadaptasi dan memenuhi semua tuntutan abad 21. Pada kurikulum 2013 diharapkan dapat diimplementasikan pembelajaran abad 21. Hal ini untuk menyikapi tuntutan zaman yang semakin kompetitif. Adapun pembelajaran abad 21 mencerminkan empat hal. 1) Critical Thinking dan Problem Solving, 2) Communication Skills, 3) Collaboration Skills, 4) Creativity Skills dan Innovation. Tuntutan dunia internasional terhadap tugas guru memasuki abad ke-21 tidaklah ringan. Guru diharapkan mampu dan dapat menyelenggarakan proses pembelajaran yang bertumpu dan melaksanakan empat pilar belajar yang dianjurkan oleh Komisi Internasional UNESCO untuk Pendidikan, hal ini didasari bahwa Pendidikan merupakan komunikasi terorganisasi dan berkelanjutan yang dirancang untuk menumbuhkan kegiatan belajar pada diri peserta didik (education as organized and sustained communication designed to bring about Learning).Kata kunci: Pembelajaran abad 21, Kurikulum 2013, 4C.ABSTRACTThe 21st century is marked by the development of information, computing, automation, and communication which penetrated in all aspects of human life in all parts of the world. This certainly has an impact on applied education including how the learning model can adapt and meet all the demands of the 21st century. In the 2013 curriculum it is expected to be implemented 21st century learning. This is to respond to the demands of an increasingly competitive era. The 21st century learning reflects four things. 1) Critical Thinking and Problem Solving, 2) Communication Skills, 3) Collaboration Skills, 4) Creativity Skills and Innovation. The international demand for teacher assignments into the 21st century is not easy. Teachers are expected to be able and able to organize a learning process that is based and implement the four pillars of learning recommended by the UNESCO International Commission for Education, this is based on that Education is an organized and sustainable communication designed to foster learning activities in students (education as organized and sustained) communication designed to bring about Learning).Keywords: 21st Century Learning, Curriculum, 4C; Communication Skill